The Energy Amplification Characteristic Research of a Multimodal Actuator. (18th May 2016) - Yali, Han; Dabin, Hao; Yu, Shi; Songqing, Zhu; Zhou, Zhou
A multimodal actuator is proposed to fulfil the different walking patterns of a power-assisted knee exoskeleton. With this actuator, the exoskeleton leg can realize several modes of operation, including series elastic actuation, stiff position control and energy storage and release. The energy amplification characteristics of the multimodal actuator in the series elastic mode are analysed. A dynamics model was established to study how series elasticity and the equivalent mass of transmission influence a power source, such as an electric motor. The results, in both simulation and experiment, show that series elasticity can amplify actuator power output, and the power output of a multimodal actuator is greater when the equivalent mass of the transmission mechanism is smaller. This research into multimodal actuator energy amplification supplies important insights into the design of artificial systems that can more closely approximate the performance of biological systems.